Implementation of the Algorithm Fisher Yates Shuffle on Game Quiz Environment - widi aulia rohmah; Asriyanik Asriyanik; Winda Apriyandari (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
The current technological development of science and knowledge can easily be provided through various media. Learning media have become part of the learning and teaching process. In its use these media can be anything such as videos, motion animations, power points, including games. Educational games can be used as learning media in schools so that learning activities can be more interesting and enjoyable. Games made as learning media are certainly not merely entertainment but must contain elements and educational values. The purpose of this research is to make an educational game of natural science where the questions / questions in the quiz section can be scrambled by themselves. The design of the construction of this environmental quiz game uses the method of Multimedia Development Life Cycle (MDLC) and Fisher Yates Shuffle algorithm for randomization of questions. This environmental game contains natural science lessons about the organization of life systems, the interaction of living things with the environment and environmental pollution. Components in this game are in the form of material and quiz games, puzzles and drag and drop. In this study there are 10 questions that will be randomized to each quiz. The result of the implementation of the Fisher Yates Shuffle algorithm in this quiz section is that the quiz questions that come out can be scrambled, so the questions / questions that come out are different and the user does not easily guess the next question.Keywords: Quiz Game, Adobe Flash, Actionscript, Fisher Yates Shuffle